1984
DOI: 10.3758/bf03333748
|View full text |Cite
|
Sign up to set email alerts
|

Object recognition as a function of stimulus characteristics

Abstract: Twenty-five college students were tested for recognition memory of small common objects immediately after exposure and after a retention interval of 1 week. The objects were classified into three object types based upon a cluster analysis of rated stimulus characteristics. The results indicated that recognition performance was influenced by object type and retention interval. The importance of considering stimulus characteristics in theoretical explanations of memory for environmental detail was discussed. Ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

1984
1984
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
4
0
2
Order By: Relevance
“…g the homogen eou s slides are accen tuated and po stexp en men t discussions with subjects co nfirmed this . Barnard, Breeding, and Cross (1984) have recen tly observ~d that the reco gnition of objects (shown directly rather than.pICtorially) and the decline of reco gnition for these same objects over a l-w eek retention interval are partially dep endent upon specific object characteristics as revealed by cluster an~lysis ?f rated stimulus dimensions. The present results provide still ano ther factor, the homogeneous or het ero gen eous nature of the context in which complex homogeneous pictures are originall y viewed whi ch influences subsequent recognition performance.…”
Section: Discussion Proceduresmentioning
confidence: 99%
“…g the homogen eou s slides are accen tuated and po stexp en men t discussions with subjects co nfirmed this . Barnard, Breeding, and Cross (1984) have recen tly observ~d that the reco gnition of objects (shown directly rather than.pICtorially) and the decline of reco gnition for these same objects over a l-w eek retention interval are partially dep endent upon specific object characteristics as revealed by cluster an~lysis ?f rated stimulus dimensions. The present results provide still ano ther factor, the homogeneous or het ero gen eous nature of the context in which complex homogeneous pictures are originall y viewed whi ch influences subsequent recognition performance.…”
Section: Discussion Proceduresmentioning
confidence: 99%
“…The order of mapping condition was counterbalanced across groups. Evidence of retention and the effects of prior learning were assessed by repeating the test 1 week later (Barnard, Breeding, & Cross, 1984). The duration of each session was 30 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the finding (Barnard et al, 1984) that the judged characteristics of objects may influence how they are subsequently recognized, in a way different from words, should provide a caution against the acceptance of picture recognition as simply as extension of the principles of verbal recognition memory. Horton and Mills (1984), in their review, maintained that the current evidence is that pictures and words are dealt with differently in memory even though this fact may not preclude a single memory system.…”
Section: Discussionmentioning
confidence: 90%
“…A recent study by Barnard, Breeding, and Cross (1984) supported the Goldstein and Chance (1974) admonition that the nature of the stimuli be considered. Barnard et al found that the informational characteristics of exhibited objects, as revealed by cluster analysis, were important determiners of how such objects were later recognized.…”
mentioning
confidence: 99%